Modelling neurodegeneration and inflammation in early diabetic retinopathy using 3D human retinal organoids - de Lemos, Luisa (2024)
PURPOSE: Diabetic retinopathy (DR) is a complication of diabetes and a primary cause of visual impairment amongst working-age individuals. DR is a degenerative condition in which hyperglycaemia results in morphological and functional changes in certain retinal cells. Existing treatments mainly address the advanced stages of the disease, which involve vascular defects or neovascularization. However, it is now known that retinal neurodegeneration and inflammation precede these vascular changes as early events of DR. Therefore, there is a pressing need to develop a reliable human in vitro model that mimics the early stage of DR to identify new therapeutic approaches to prevent and delay its progression. METHODS: Here, we used human-induced pluripotent stem cells (hiPSCs) differentiated into three-dimensional (3D) retinal organoids, which resemble the complexity of the retinal tissue. Retinal organoids were subjected to high-glucose conditions to generate a model of early DR. RESULTS: Our model showed well-established molecular and cellular features of early DR, such as (i) loss of retinal ganglion and amacrine cells; (ii) glial reactivity and inflammation, with increased expression of the vascular endothelial-derived growth factor ( VEGF) and interleukin-1β ( IL-1β), and monocyte chemoattractant protein-1 (MCP-1) secretion; and (iii) increased levels of reactive oxygen species accompanied by activation of key enzymes involved in antioxidative stress response. CONCLUSION: The data provided highlight the utility of retinal organoid technology in modelling early-stage DR. This offers new avenues for the development of targeted therapeutic interventions on neurodegeneration and inflammation in the initial phase of DR, potentially slowing the disease's progression. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s44164-024-00068-1.